Dicionário biográfico universal de autores - dir. Luis Albuquerque (Artis - Bompiani, 1966)
1.º vol.: A - C, 838 p.; 2.º vol.: D - K, 1725 p.; 3.º vol.: L - O, 2485 p.; 4.º vol.: P - S, 3422 p.; 5.º vol.: T - Z, 4029 p.